2014
DOI: 10.1111/jeb.12347
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effects of contemporary and historical range expansion on the distribution of genetic diversity in the damselfly Coenagrion scitulum

Abstract: Although genetic diversity provides the basic substrate for evolution, there are a limited number of studies that assess the impact of recent climate change on intraspecific genetic variation. This study aims to unravel the degree to which historical and contemporary factors shape genetic diversity and structure across a large part of the range of the range-expanding damselfly Coenagrion scitulum (Rambur, 1842). A total of 525 individuals from 31 populations were genotyped at nine microsatellites, and a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 75 publications
(97 reference statements)
1
18
1
Order By: Relevance
“…The number of generations presented here may seem low and may raise questions regarding our ability to detect the signature of a bottleneck or other effects of genetic drift. However, results from previous studies suggest otherwise (e.g., Garroway et al 2011, Harper 2011, Short and Petren 2011, Swaegers et al 2014. Our study provides evidence that continuous gene flow from conspecifics may prevent the loss of genetic diversity from recently established populations at the edge of a species' range.…”
Section: Evidence Of Continuous Gene Flowcontrasting
confidence: 42%
See 2 more Smart Citations
“…The number of generations presented here may seem low and may raise questions regarding our ability to detect the signature of a bottleneck or other effects of genetic drift. However, results from previous studies suggest otherwise (e.g., Garroway et al 2011, Harper 2011, Short and Petren 2011, Swaegers et al 2014. Our study provides evidence that continuous gene flow from conspecifics may prevent the loss of genetic diversity from recently established populations at the edge of a species' range.…”
Section: Evidence Of Continuous Gene Flowcontrasting
confidence: 42%
“…Sakai et al (2001) suggested that maintaining genetic diversity in a recently established population is essential for successful establishment and growth of that population. Previous studies have found that new populations in recently colonized areas on the periphery of source populations exhibit fine-scale genetic structure, lower genetic diversity, and allelic frequency gradients in the direction of range expansion (e.g., House Swaegers et al 2014). Of the empirical studies referenced here, 4 of the 6 investigated genetic diversity and population structure in a species that underwent range expansion beginning in the 1990s, the same time period when the Virginia's Warbler was documented as having expanded its range into the Black Hills of South Dakota.…”
Section: Evidence Of Continuous Gene Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed a detailed spatiotemporal genetic analysis of the range expanding damselfly C. scitulum along a coastal axis during the first years after colonisation. The two novel key findings of the current study that extend previous insights obtained in the large‐scale study of this range expansion (Swaegers et al ., , ) are that (i) the spatial dynamics indicate founder effects and a major contribution from the broad expansion front during the colonisation of the coastline rather than a stepping‐stone colonisation process and (ii) the fine‐scale temporal dynamics do not reflect persistent founder effects and instead show considerable temporal instability in genetic indices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Swaegers et al (40,41), studying genetic diversity and structure of the damselfly Coenagrion scitulum, used a combination of mitochondrial gene sequencing, microsatellite analyses, and single-nucleotide polymorphisms across the entire species' range to disentangle the role of historical range expansions from the effect of recent range shifts due to global warming. Their multilocus polygenic analysis identified candidate loci potentially under thermal selection, and their studies highlight the usefulness of integrating genomic, phenotypic, and environmental data to disentangle historical and contemporary evolutionary and ecological processes.…”
mentioning
confidence: 99%